Late Holocene Changes in Erosion Patterns in a Lacustrine Environment: Landscape Stabilization by Volcanic Activity Versus Human Activity. (2nd April 2019) - Lamair, Laura; Hubert‐Ferrari, Aurélia; El Ouahabi, Meriam; Yamamoto, Shinya; Schmidt, Sabine; Vander Auwera, Jacqueline; Lepoint, Gilles; Boes, Evelien; Fujiwara, Osamu; Yokoyama, Yusuke; De Batist, Marc; Heyvaert, Vanessa M. A.
Abstract: The most recent eruption of Mount Fuji (Japan), the VEI 5 Hōei plinian eruption (CE 1707) heavily impacted Lake Yamanaka, a shallow lake located at the foot of Mount Fuji. Here we discuss the influence of the Hōei eruption on the lacustrine sedimentation of Lake Yamanaka using high‐resolution geophysical and geochemical measurements on gravity cores. Hōei scoria fallout had two major impacts on Lake Yamanaka: (i) reduction of the sedimentation rate (from 0.16 to 0.09 cm/year) and (ii) the increase of in situ lake productivity. Sedimentation rates after the eruption were relatively low due to the thick scoria layer, trapping underlying sediments in the catchment. The lacustrine system took more than 170 years to begin to recover from the Hōei eruption: most recently sedimentation recovery has been accelerated by changes in land use. Since the beginning of the twentieth century, vegetated strips delimited cultivated parcels, trapping sediment and minimizing anthropogenic impacts on the sedimentation rate. Over the last decade, the decline of agriculture and the increase of other human activities has led to an increase in the sedimentation rate ( 1 cm/year). This study highlights the effect of the grainsize of the volcanic ejecta on the sedimentation rate following a volcanic eruption. Coarse‐grained tephra are difficult to erode. Therefore, their erosion and remobilization is largely limited to intense typhoons when porous scoria deposits are saturated by heavy rains. Moreover, this study suggests that recent anthropogenic modifications of the catchment had a greater impact on the sedimentation rate than the Hōei eruption. Key Points: Decrease of sedimentation rate is in Lake Yamanaka observed following scoria fallout Lake Yamanaka's sedimentary system took over 170 years to recover its initial sedimentation rate Anthropogenic modifications of the catchment have a greater impact than a major Plinian eruption of Mount Fuji on the sedimentation rate